Analysis of the Investment Funds Development in Poland in 2003–2007 - Maciej Świda (Contemporary Economics)
The article presents results of analysis of the investment funds market in Poland in 2003–2007. The analysis was basically made in main groups of the investment funds. In the article are presented the data, which described changes on capital market and in portfolio structure of the investment funds. It is a base for the investment funds market general assessment.